How COVID-19 pandemic has changed elective surgery: the experience in a general surgery unit at a COVID-hospital - Giuffrida, Mario; Cozzani, Federico; Bonati, Elena; Del Rio, Paolo (Acta Biomedica Atenei Parmensis, 2021)
Objective: Evaluate the impact of Covid-19 in a critical area and analyze the changes in the daily activities in a General Surgery Unit of a tertiary Covid-Hospital. Methods: We report and compared all the surgical procedures performed between two periods (March and April 2019 and March and April 2020) at General Surgery Department of Parma University Hospital, a tertiary Covid-Hospital.Results: Between March and April 2019, a total of 232 surgical procedures were performed. Between March and April 2020 only 61 surgical procedures were performed. In 2019 84 patients underwent surgery for cancer and 171 underwent surgery for benign diseases. In 2020 only 37 patients underwent surgery for oncological reasons and 24 underwent surgery for benign diseases. Conclusions: During pandemic Covid-19 the access to health services was limited and poor. Limited access to health services and the fear of Covid-19 infection can explain the lower number of elective surgical procedures for cancer in 2020 compared to the same period in the 2019.